Project-Based (PjBL) and Guided Inquiry Learning: Students’ Response to Rectilinear and Circular Motion Phenomena - Rismawati, Rismawati; Sarwanto, Sarwanto; Saputro, Budiyono (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2019)
The learning method is one of the essential factors that influence the success of learning. To build good quality learning, choosing the right method is a crucial step. This study aims to identify differences in student learning achievement by applying two learning methods, project-based learning (PjBL) and guided inquiry (GI) in rectilinear motion and circular motion. The quasi-experimental method was used in this study. The participants were selected by cluster random sampling consisting of two classes (36 students and 35 students) from one of the Vocational Schools in Surakarta. Data collected through multiple-choice tests and interviews were analyzed in descriptive and inferential statistics using ANOVA and t-test. The results show that there is an influence of the learning method on student learning achievement in which both the PjBL and GI method. Students who learned rectilinear motion and circular motion using PjBL got higher scores than the GI method. The implication of this research is as a teacher's reference in choosing learning methods relevant to the rectilinear motion and circular motion and its implementation is expected to improve student learning achievement.